Exploring the Biochemical Basis of the Meridian Tropism Theory for the Qi-Invigorating Traditional Chinese Medicine Herb - Mengmei Li MD; Yu Chen MD; Zhongzhen Cai MD; Jie Teng MD; Qian Feng MD; Yuming Chen PhD; Lin Wang MD; Caixia Li MD; Bruce Qing Tang PhD; Xuemei Bai PhD (SAGE Publishing, 2021)
We examined the effect of the Qi-invigorating Traditional Chinese Medicines (TCM) herb Panax ginseng ( P.G. ) on mitochondrial functions and cellular antioxidant capacity in different organs of mice. We found that the P.G. extracts had a significant effect on tissues of mice, with the generation of total adenylate pool (TAP) enhanced in all visceral tissues, but not for the brain. The mitochondrial membrane potential (MMP) and antioxidant capacity reflected by superoxide dismutase (SOD) and glutathione (GSH) increased only for the meridian tissues that P.G. belongs to including Heart, Spleen and Lung. Reactive oxygen species (ROS), as a combined result of the increased energy metabolism and antioxidant capacity, varied in different organs. We concluded that: 1) the Qi-invigorating TCM herb P.G. had a significant effect on mice by enhancing TAP production in all of the visceral tissues examined, except for the brain; 2) for the meridional tissues of P.G. (Heart, Spleen and Lung), the P.G. extracts not only promoted the TAP production, but also boosted the antioxidant capacity demonstrated by the simultaneous increase in TAP, and SOD and GSH.